Budaya Gunung dalam Hikayat Wayang Pandu Karya Muhammad Bakir: Telaah Kedudukan Gunung dalam Teks Naratif - Riqko Nur Ardi Windayanto (Manuskripta, 2024)
This research aims to reveal the mountain culture in the Hikayat Wayang Pandu by Muhammad Bakir by using tandem narratology and cultural geography. Textual and contextual studies are the building methodology. The mountains become the locations for the actors to learn and teach, meditate and express gratitude, and become priests after giving up the kingship. These are caused by the mountains’ positions in the actor’s understanding as a space for the circulation of knowledge, a sacred space, and a space for achieving asceticism. These simultaneously show the opposition and integration between mountains and countries (kingdoms), which place mountains as a location for accumulating capital for power and giving it up. The presence of mountains is parallel to texts from the same tradition and other traditions as well as Java’s environment. The author also presents new mountains as a form of creativity of the 19th century. Thus, mountains are not only natural, but also cultural spaces that have discursive positions as a geographical context for carrying out various cultural activities. === Penelitian ini bertujuan untuk mengungkapkan budaya gunung dalam Hikayat Wayang Pandu karya Muhammad Bakir dengan naratologi dan geografi budaya sebagai teori tandem. Kajian tekstual dan kontekstual menjadi bangunan metodologis. Gunung-gunung dalam hikayat ini menjadi lokasi para aktor untuk belajar mengajar, bertapa dan menyampaikan rasa syukur, serta menjadi begawan setelah mengakhiri kekuasaan. Ketiganya merupakan budaya gunung yang direpresentasikan oleh teks karena kedudukan gunung dalam pemahaman aktor merupakan ruang sirkulasi pengetahuan, ruang suci, dan ruang untuk mencapai asketisme. Ketiganya menunjukkan oposisi sekaligus integrasi antara gunung dan negeri (kerajaan), yang menempatkan gunung sebagai lokasi untuk mengakumulasi modal kekuasaan dan mengakhirinya. Kehadiran gunung-gunung dalam hikayat ini paralel dengan teks-teks setradisi dan tradisi lain serta lingkungan Jawa. Pengarang juga menghadirkan gunung-gunung baru sebagai bentuk kreativitas abad ke-19. Dengan demikian, gunung bukan hanya ruang alam, melainkan juga ruang kultural yang memiliki kedudukan diskursif dalam teks sebagai konteks geografis terselenggaranya berbagai aktivitas budaya.